Sequential chimeric medial femoral condyle and anterolateral thigh flow-through flaps for one-stage reconstructions of composite bone and soft tissue defects: report of three cases - Henn, Dominic; Hirche, Christoph; Hernekamp, Jochen-Frederick; Schmidt, Volker-Jürgen; Kneser, Ulrich; Kremer, Thomas (Microsurgery, 2017)
Small recalcitrant non-unions with poor perfusion require reconstruction with vascularized bone flaps. Cases with concomitant large soft tissue defects are especially challenging, since vascularized soft tissue transfer is often indicated and distant microvascular anastomoses may be required. We introduce a sequential chimeric free flap composed of a medial femoral condyle corticoperiosteal flap anastomosed to an anterolateral thigh flow-through flap (MFC-ALT flap) and report its use for reconstruction of small non-unions with concomitant large soft tissue defects in three exemplary patients. Two female and one male patients ages 39-58 years suffered from composite bone and soft tissue defects of the lower extremity and clavicle caused by tumor resection and postoperative radiation resp. infected tibial pilon fracture. The sizes of the soft tissue defects ranged from 15-23 × 4.5-6 cm and the sizes of the bone defects ranged from 1.5-4 × 2-4 cm. Defect reconstructions were performed in all cases with sequential chimeric MFC-ALT flaps with sizes ranging from 2-4 × 1.6-4 cm for the MFC and 21-23 × 7-8 cm for the ALT skin paddles. Functional reconstructions were achieved in all cases resulting in stable unions and soft tissue coverage enabling the patients to bear full weight without assistance on 5-months follow-up. Postoperative course was uneventful and complications were restricted to a small skin necrosis at the suture line in one case. MFC-ALT flaps may be a safe, and effective procedure for one-stage reconstructions of small, irregularly shaped bone defects with concomitant large soft tissue loss or surrounding instable scarring, particularly in cases of recalcitrant non-unions after radiation exposure.